A structural semiotic approach to the Quranic character of Yunus, peace be upon him, and the aesthetics of place in the Quranic story - Rayyan, Mahmoud Jamal (Journal of Arabic Language Sciences and Literature, 2025)
The semiotics of the literary character is one of the branches of linguistic semiotics, which paves the way to highlight the personality in a more profound and accurate way to reveal hidden angles within it. The Glorious Quran, as the most prominent and wonderful literary text, carries within it tremendous linguistic signs, and many characters mentioned directly in the Glorious Quran are considered important linguistic signs. It is worth mentioning that Yunus, peace be upon him, is one of the important characters mentioned in the Glorious Quran, and here his study comes in a semiotic direction that leads to revealing the meanings, concepts and connotations that this character carries. This article studied the character of Yunus (peace be upon him) from a semiotic perspective based on the theory of the French semiotician Philippe Hamon, where it studied the character of Yunus (peace be upon him) from the aspect of the signifier (the noun, the grammatical role, the pronouns, and the rhetorical dimension), and from the aspect of the connotation (the attributes and verbs). It has been proven that there is a consistency between the name of Yunus (peace be upon him) and the descriptions he carries and his roles in the Qur’anic story, as if the Qur’an aims to present the Qur’anic character in general, and the character of Yunus (peace be upon him) as a model and symbol of how to believe in God Almighty in various circumstances. We also discussed in our research the aesthetics of place in the story of Yunus (peace be upon him), and we proved that place has its semiotic and actual role in creating the narrative, as the imaginary narrative has a role in adding privacy to the real space that houses the Quranic character, which in turn moves and takes center stage according to the place it takes refuge in on its journey. We divided the two types of places; referential and miraculous into safe and frightening places, and the circularity of place was achieved in a way that suits the character’s transformations on its journey through its various stations; thus, the places of security and fear were equal to the character’s actions. The place, with all its aesthetics, was transformed into an indicator of the character’s advantages, and its actions were marked by the characteristics of the place in which it settled and mixed with it, in its missionary transformations, arriving at stability, and salvation in the end.